2018
DOI: 10.1093/ajcp/aqy066
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Bone Marrow Sampling and Core Biopsy Specimen Adequacy in the United States and Canada

Abstract: CL is shorter than recommended and varies with patient age and sex, clinical circumstances, and center experience. While pathologists render diagnoses on most cases irrespective of CL, BMB yield improvement is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Cellularity is best evaluated from the biopsy, ideally ≥ 1.5 cm in length without crush artifact 15 ; however, in many practice settings biopsies are usually smaller. 26 Clot sections are suboptimal, but can be used if they have moderately sized spicules ≥ 0.2 cm. Aspirate smears can only give a qualitative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Cellularity is best evaluated from the biopsy, ideally ≥ 1.5 cm in length without crush artifact 15 ; however, in many practice settings biopsies are usually smaller. 26 Clot sections are suboptimal, but can be used if they have moderately sized spicules ≥ 0.2 cm. Aspirate smears can only give a qualitative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 11 ] In contrast, a recent study of 6374 marrow specimens from 32 academic centers showed only 4% of the bone marrow biopsies and 2% of the bone marrow biopsy/bone marrow aspirate samples inadequate for diagnosis. [ 12 …”
Section: Introductionmentioning
confidence: 99%
“…Synoptic reporting, using standardized checklists and data elements, is widely accepted to improve the accuracy and completeness of pathology reports[ 13 ] and this format has been facilitated by the cancer checklists and guidelines developed by the CAP. [ 12 13 ] Based on the CAP checklist, Murari and Pandey proposed synoptic reporting system for bone marrow specimens, in 2006, and a similar synoptic system for hematological and lymphoid neoplasms was devised by Mohanty et al . [ 14 15 ] Detailed guidelines for the application of the checklist in synoptic bone marrow reporting were subsequently published by the CAP Pathology and Laboratory Quality Center.…”
Section: Introductionmentioning
confidence: 99%
“…152 If both marrow cytology and marrow architecture are needed, separate aspiration and core biopsies are recommended. 153,154 Of note, in an extensive survey from 2001 to 2011 of 6374 bone marrow samples in 32 academic centers, adequacy remained a major concern, with adequacy criteria for CNB centered on core biopsy length and capacity for morphologic evaluation. 154 Altogether, 11% of CNBs were noncontributory.…”
Section: Bone Marrowmentioning
confidence: 99%
“…153,154 Of note, in an extensive survey from 2001 to 2011 of 6374 bone marrow samples in 32 academic centers, adequacy remained a major concern, with adequacy criteria for CNB centered on core biopsy length and capacity for morphologic evaluation. 154 Altogether, 11% of CNBs were noncontributory. In part this can be attributed to the observation that on average only 74% of the biopsies contained evaluable bone marrow.…”
Section: Bone Marrowmentioning
confidence: 99%